Sofijska polonistyka i współczesne bułgarskie polonofilstwo - Kamen Rikew (Postscriptum Polonistyczne)
The paper gives an overview of the history and presentday status of Polish studies at St Kliment Ohridski University in Sofia and discusses several key aspects of Polish cultural presence in contemporary Bulgaria. It explains the specific structure of Polish philology studies at the University in the light of the country’s modern educational system and highlights the most prominent scholars that have shaped the prestige of this particular branch of Slavistics.